Probabilistic Tsunami Hazard and Risk Analysis: A Review of Research Gaps - Behrens, Jörn; Løvholt, Finn; Jalayer, Fatemeh; Lorito, Stefano; Salgado-Gálvez, Mario A.; Sørensen, Mathilde; Abadie, Stephane; Aguirre-Ayerbe, Ignacio; Aniel-Quiroga, Iñigo; Babeyko, Andrey; Baiguera, Marco; Basili, Roberto; et al. (Frontiers in Earth Science, 2021)
Tsunamis are unpredictable infrequent but potentially large impact natural disasters. To prepare, mitigate and prevent losses from such catastrophes, probabilistic hazard and risk analysis methods have been developed and have proved useful. However, large gaps and uncertainties still exist and many steps in the assessment methods lack information, theoretical foundation, or commonly accepted methods. Moreover, applied methods have very different levels of maturity, from already advanced probabilistic tsunami hazard analysis for earthquake sources, to less mature probabilistic risk analysis. In this review we give an overview of the current state of probabilistic tsunami hazard and risk analysis. Identifying research gaps, we offer suggestions for future research directions. An extensive literature list allows for branching into diverse aspects of this scientific approach.